Experimental study and theoretical modeling for the compressive stress-strain relationship of multi-scale hybrid fiber-reinforced SHCC - Zhang, C. (2022)
In order to better match the multi-level structural characteristics and multi-scale fracture process of cementitious composite, multi-scale hybrid fiber-reinforced strain hardening cementitious composite (MsHySHCC) was designed by adding hooked steel fiber and calcium carbonate (CaCO3) whisker into conventional polyvinyl alcohol (PVA) fiber-reinforced SHCC. Compressive properties of PVA-SHCC and MsHySHCC were evaluated experimentally. The results indicate that the designed MsHySHCC had a better compressive performance than that of PVA-SHCC. Moderately partially substituted PVA fibers by steela fiber and CaCO3 whisker enhanced the compressive parameters, however, further substitution of PVA fibers by increasing the content of CaCO3 whisker didn’t bring a higher promotion. Two kinds of semi-theoretical compression constitutive models were developed from the perspective of damage mechanics theory and geometrical mathematical description, respectively. It was found that both of the proposed models can be applied to predict the uniaxial compressive stress-strain relationships of PVA-SHCC and MsHySHCCs.